Isolation of Acanthamoeba-Specific Antibodies from a Bacteriophage Display Library - Khan, Naveed A. (American Society for Microbiology, 2000)
Acanthamoeba causes opportunistic eye infections in humans, which can lead to severe keratitis and may ultimately result in blindness. Current methods for identifying this organism rely on culture and microscopy. In this paper, we describe the isolation of antibody fragments that can be used for the unequivocal identification of Acanthamoeba. A bacteriophage antibody display library was used to isolate antibody fragments that bind specifically to Acanthamoeba. Individual clones were studied by enzyme-linked immunosorbent assay, flow cytometry, and immunofluorescence. Four antibody clones that specifically bind to Acanthamoeba spp. were identified.